Gender difference as a major determinant of creative behaviour among junior secondary school students in Oyo, Osun and Ogun States, Nigeria (2011)
It is interesting to note that the government of Nigeria has become increasingly aware of the need to nurture creative Nigerian children. Government awareness has been partly informed by the need to implement the National Policy on Education, including the aspect that has to do with special education. It. should be borne in mind that one of the objectives of special education as stipulated in the National policy on Education is that opportunities will be provided for creative children to develop at their own pace in the interest of the nation's economic and technological development. This awareness has been further reinforced by Government's pronouncements on the need for the education of creative Nigerian. There is a strong argument in the literature that creative people are capable of launching the society into the much-desired technological age and that creativity is a highly valued behaviour. There is also very strong evidence in the literature that certain factors determine creative behaviour (Sylvia, 2000). According to Sylvia, some of the factors that determine creative behaviour include: Peer pressure, Attitudinal disposition of teachers and Gender. For the purpose of this study, attention was focused on Gender difference as a major determinant of creative behaviour. The study adopted 'ex-post facto' research design. Stratified random sampling technique was used for the selection of 1,800 respondents out of 2,620 representing 69 percent of the total population. The mean age for the participants was 13.49 years. Data were collected using two valid and reliable research instruments namely: Ibadan Creativity Assessment Scale ( ICAS) a — 0.76 and Creative Behaviour Determinant Scale ( CBDS) a = 0.84. The data were analysed using t-test. The findings showed that there was no significant difference between male and female students and their creative behaviour (t=13; df=1798; p >. 05).